2019
DOI: 10.1111/een.12809
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical defences and performance of specialist and generalist herbivores: a meta‐analysis

Abstract: 1. Phytochemical coevolution theory, a long-standing paradigm in plant-insect interactions, predicts that specialist herbivores are less negatively affected by the allelochemicals of their host plants than are generalist herbivores. Although this theory is prevalent in plant-insect science, it is not always supported by empirical studies measuring the performance of specialist and generalist insects in response to allelochemicals.2. The present study aimed to investigate: (i) whether there a difference between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…For example, how do plants respond to highly specialized herbivores, and are such adapted consumers immune to plant defenses? On average, specialists are less impacted by particular plant defense compounds than generalists (1,2), but does this mean that further coevolution is not possible? Even highly specialized herbivores must contend with plant defenses if coevolutionary interactions are proceeding (3).…”
Section: Introductionmentioning
confidence: 99%
“…For example, how do plants respond to highly specialized herbivores, and are such adapted consumers immune to plant defenses? On average, specialists are less impacted by particular plant defense compounds than generalists (1,2), but does this mean that further coevolution is not possible? Even highly specialized herbivores must contend with plant defenses if coevolutionary interactions are proceeding (3).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the terms 'generalist' and 'specialist' may also oversimplify a continuous spectrum of insect diet breadth (Loxdale and Harvey 2016). Rothwell and Holeski (2020) conducted a meta-analysis incorporating 45 studies and found evidence that specialist insects do outperform generalists in terms of growth, but not fecundity or survival. However, the need remains for further consideration of insects occupying the middle portion of the diet breadth spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…be better adapted to the secondary metabolites of their host plants than generalist herbivores (Stamp, 2003;Loxdale et al, 2011), although this prediction has been increasingly debated in recent years (Ali and Agrawal, 2012;Smilanich et al, 2016;Rothwell and Holeski, 2019). To our surprise, the generalist S. frugiperda performed better on some of the landraces that had higher phenolic content, whereas the specialist C. multifenestrata performed best on the cultivated "Hass."…”
Section: Avocado Domestication On Resistance Traitsmentioning
confidence: 91%